Cell alignment guided by nano/micro oriented collagen fibers and the synergistic vascularization for nervous cell functional expression. (June 2018) - Wei, Dan; Sun, Jing; Yang, You; Wu, Chengheng; Chen, Suping; Guo, Zhenzhen; Fan, Hongsong; Zhang, Xingdong
Abstract: The majority of tissues within human body are constituted of designated structures to enable specific functions. Much effort has been done to engineer artificial fabric cell-laden scaffolds which are widely used for a great diversity of linear tissue constructs. For this purpose, collagen microfibers are of great concern among diverse materials while the control of cell-laden fiber formation and orientated structure is still unsolvable. Here, we developed a novel microfluidic-based strategy for continuous fabrication and assembly of three-dimensional (3D) cell-laden oriented collagen hydrogel microfibers. Inspired by the flow-introduced shear force in a microfluidic chip, collagen hydrogel microfibers obtained the oriented fabric structure which could guide rat pheochromocytoma cells (PC12) oriented spreading and enhance relative cellular functional expression. Rat aortic endothelial cells (RAOECs) were introduced to construct a co-cultured microfiber model, which further facilitated the functional expression of neural cells due to the synergistic effect of both vascularized-like cells and neural-like cells. Moreover, the ability of assembling collagen microfibers into larger constructs will benefit a variety of applications in tissue engineering and biomedical research. Highlights: Develop a facile microfluidic-based strategy for continuous fabrication of oriented cell-laden collagen hydrogel microfibers. Introduce a rotary receiving pool to enhance the alignment of collagen hydrogel microfibers. Demonstrate microfibers with orientated structure could guide neural cells align and promote their functional expression. Introduce RAOECs to construct a co-culture model to further facilitate the functional expression of neural cells. Explore a high-efficient and potential approach for regenerating large tissue of complex anatomical structures.